2020
DOI: 10.1002/jmri.27249
|View full text |Cite
|
Sign up to set email alerts
|

Resting‐State Power and Regional Connectivity After Pediatric Mild Traumatic Brain Injury

Abstract: Background: Physiological recovery from pediatric mild traumatic brain injury (pmTBI) as a function of age remains actively debated, with the majority of studies relying on subjective symptom report rather than objective markers of brain physiology. Purpose: To examine potential abnormalities in fractional amplitude of low-frequency fluctuations (fALFF) or regional homogeniety (ReHo) during resting-state fMRI following pmTBI. Study Type: Prospective cohort. Population: Consecutively recruited pmTBI (N = 105; 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 57 publications
(121 reference statements)
3
10
0
Order By: Relevance
“…Although highly speculative, it is tantalizing to elaborate on a possible protective effect of compromised UF microstructure regarding the development of persistent symptoms via the presence of less emotional awareness. In line with our results, previous diffusion and resting‐state fMRI studies have shown null findings with respect to persistent symptoms in pediatric and adult mTBI (Ilvesmaki et al., 2016; Stephenson et al., 2020; Wäljas et al., 2014). Other studies have reported diffusion abnormalities in the same tracts that were examined in our study, and that these abnormalities were related to PTS (Aoki & Inokuchi, 2016; Dodd et al., 2014; Hellstrøm et al., 2017; King et al., 2019; Mayer et al., 2010; Wallace et al., 2020).…”
Section: Discussionsupporting
confidence: 91%
“…Although highly speculative, it is tantalizing to elaborate on a possible protective effect of compromised UF microstructure regarding the development of persistent symptoms via the presence of less emotional awareness. In line with our results, previous diffusion and resting‐state fMRI studies have shown null findings with respect to persistent symptoms in pediatric and adult mTBI (Ilvesmaki et al., 2016; Stephenson et al., 2020; Wäljas et al., 2014). Other studies have reported diffusion abnormalities in the same tracts that were examined in our study, and that these abnormalities were related to PTS (Aoki & Inokuchi, 2016; Dodd et al., 2014; Hellstrøm et al., 2017; King et al., 2019; Mayer et al., 2010; Wallace et al., 2020).…”
Section: Discussionsupporting
confidence: 91%
“…fALFF is also associated with increased metabolism in cortical regions. Higher fALFF and metabolism in cortical areas could be interpreted as representing a potential compensatory response to the damage in patients suffering from trauma ( Stephenson et al, 2020 ). In line with this, a recent study in patients with severe TBI showed higher ALFF in the right temporal, frontal, and IPC in the conscious subgroup compared with the coma subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, rs-fMRI was used to provide insight into areas of the brain that are synchronously active at rest in the absence of any particular cognitive stimuli) to explore the functional neuropathology of concussion. While the brain regions and/or networks studied, time of imaging, and rs-fMRI analysis methods themselves have varied across studies, studies consistently show that there are rs-fMRI disturbances in children with concussion in comparison to their healthy peers 12-23 . Collectively, these studies have shown patterns of both hyper-and hypo-connectivity within the initial weeks of injury 24 , abnormal rs-fMRI activity in children with protracted symptoms 15 , and a persistence of functional impairment in asymptomatic children who have been medically cleared to return-to-sport 21 .…”
Section: Introductionmentioning
confidence: 99%